Strategi Persaingan PT Reka Piranti Prakarsa - , Ahmad Setiawan, Drs. Ahmad Jamli, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
, For entrepreneurs or top executives of the company, competing or competition is a word that is closely attached to each their daily activities. For that needs to be carefully competitive strategy is needed, it is necessary to make a breakthrough which has the advantage didandingkan competitors. This is what must be done to be able to exist in the business that they do. Moreover, the business they work is the field of Information Technology as practiced by PT. Reka Piranti Prakarsa (RPP). Moreover RPP for nearly six years running without having competitors as sole distributor. This situation may affect the available resources, they become quickly dissatisfied with the results it achieves. Attempts to create 'value' for the company and it feels like a modest weight when the company suddenly faced with competitive conditions. Problems arise when faced with the competition, especially competition was a regional player that has several networks in Asia, Australia, Europe and Latin America. The company has headquarters in the United States and is listed on the New York Stock Exchange. How to compete with the big players, the strategy of what to choose certainly makes companies have to think hard. - This paper aims to determine whether the business activities carried on by the RPP has been true in the face of competition. In addition, to identify the best strategy for addressing the RPP in the face of business development. The study was conducted by comparing the direction of the business, the theory analysis and needs a new strategy with business conditions that have been run so far. The analysis is done by using the theory of Five Forces (Porter, 1980) to find where the most can be optimized and will be the focus. To complete the analysis of the industry, I also use Coopetition and the Value Net (Brandenburger & Nalebuff, 1996). This is done to see if the possibility of co-operation can be done even with competitors. Further analysis is to conduct a PEST analysis of the macro environment - (Albert Humphrey, 1960) and the SWOT (J Francis Aguilar, 1967). Some other theories are made to support this thesis is to use the theory of Strategic Intent (Hamel and Prahalad, 1989), Core Competences (Hitt, Ireland & Hoskinson, 1995).